2007
DOI: 10.1108/01409170710823449
|View full text |Cite
|
Sign up to set email alerts
|

Holistic versus decomposed ratings of general dimensions of work activity

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…More so, it was found that performance appraisal is used as an assessment tool for promotional exercise. These findings corroborate the views of (Gibson, Harvey & Harris, 2007). Our finding that performance appraisal serves as a means for salary increment or distribution of rewards is in consonance with the views of Briscoe and Claus (2008) as well ISSN 2162-3058 2012 as Fajana (2002) who hold the view that appraisal is a means for distributing rewards.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…More so, it was found that performance appraisal is used as an assessment tool for promotional exercise. These findings corroborate the views of (Gibson, Harvey & Harris, 2007). Our finding that performance appraisal serves as a means for salary increment or distribution of rewards is in consonance with the views of Briscoe and Claus (2008) as well ISSN 2162-3058 2012 as Fajana (2002) who hold the view that appraisal is a means for distributing rewards.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…The findings of this study are consistent with the views of Gibson, Harvey & Harris (2007) who argue that performance appraisal forms the foundation for many HR functions, effectively setting the standards to drive recruiting efforts, and it is customary to use these criteria in hiring, promoting, evaluating and equitably compensating employees, and forming the basis for many employee training programmes…”
Section: International Journal Of Human Resource Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…We linked this data to O * NET occupation codes (https://www.onetonline.org/) and associated it with O * NET ’s 42 General Work Activities (GWAs). GWAs are generally summarized into “Data,” “People,” and “Things,” as confirmed by prior factor analytic work (Fine & Cronshaw, 1999; Gibson et al, 2007; Glomb et al, 2004; P. Steel et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The research began with four 'frames' or ways of looking at skill, derived from the four major approaches in the sociological literature on skill discussed above. Previous attempts to incorporate a broad range of skill indicators into a coherent framework, such as the O*NET model have not been successful (Mumford and Peterson, 1999;Gibson, Harvey & Harris, 2007). This is not surprising considering the divergent approaches to skill discussed above.…”
Section: Methodsmentioning
confidence: 99%